PENGARUH LIKUIDITAS, STRUKTUR ASET, DAN PROFITABILITAS TERHADAP STRUKTUR MODAL DENGAN FIRM SIZE SEBAGAI VARIABEL MODERASI - Nainggolan Windisari; Nasir Azwir; Natariasari Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to examine the effect of liquidity, asset structure, and profitability on capital structure and examine the effect of firm size in moderating liquidity asset structure and profitability on capital structure 2015-2019. The sampling technique used purposive sampling method. There were 43 conventional commercial banks listed on the IDX in 2015-2019. Conventional commercial banks that meet the research sample criteria are 10 companies. With an observation period of 5 years for a sample 50. From the results of the tests that have been carried out, the partial regression test (t test) shows that the profitability variable has a significant negative effect on the capital structure. Meanwhile, the liquidity and asset structure variables have no effect on the capital structure. The MRA test conducted with moderating variables shows that the liquidity variable moderated by firm size has a significant positive effect on capital structure. And the asset structure variable moderated by firm size has a significant negative effect on capital structure. While the profitability variable moderated by firm size has no effect on the capital structure.Keywords: liquidity, asset structure, profitability, capital structure, firm size